Catalytic dehydration of bio-butanol to butenes over rare earth solid catalysts - Yeong, Wei Yean. (2010)
With the depletion of non-renewable fossil fuel and increase in greenhouse gas emission, novel technologies have been explored towards converting bio-alcohols synthesized from renewable sources to produce invaluable chemical intermediates. The goal of this project focused on the development of rare earth metal crystalline catalysts and the investigation of their suitability in n-butanol dehydration to 2-butenes. Specifically, the catalytic activities of phosphates and oxides of lanthanum and cerium, in both mesoporous and non-mesoporous structures, were investigated. They were synthesized in nanoporous scale using the sol-gel method. The catalysts were characterized using XRD, CO2-TPD and NH3-TPD, FT-IR and NMR techniques. XRD confirms the formation of mesopores in the nanoparticles. NH3-TPD and CO2-TPD revealed the increase of weak acid sites and decrease in basic sites, respectively with increasing P/La molar ratio. Catalyst screening was carried out to study the activity of the catalysts over n-butanol dehydration from 473 K to 673 K. The results showed a decrease in n-butanol conversion to 2-butene in the order of CePO4 > LaPO4 > La2O3 > CeO2, with mesoporous structures giving higher 2-butenes yield. Another aim of this study was to establish the thermodynamic and kinetic modeling for the routes to propylene production. Computer simulation was used to investigate thermodynamic and kinetic parameters for ethanol and n-butanol dehydration as well as ethylene/ 2-butene metathesis. The formulation of activation energy revealed that n-butanol dehydration is a kinetically controlled reaction.